Promoção do crescimento e da produtividade de trigo pelo emprego de cepas comerciais de Trichoderma spp. - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
The fungus Trichoderma spp. is known due to its versatility for promoting crop growth and grain yield, improving the nutrient absorption and increasing the grain yield. The objective of this work was to evaluate commercial strains of Trichoderma spp. in the growth promotion and grain yield of wheat plants. The commercial strains evaluated were: Trichoderma harzianum IBLF 006 WP, Trichoderma harzianum IBLF 006 SC, Trichoderma harzianum ESALQ 1306, Trichoderma asperellum URM 5911 and an organomineral fertilizer. For this purpose, wheat seeds cv. BRS 264 were treated with 2 mL of an Trichoderma suspension (2.5 x 108 conidia mL-1 per 100 g seed) and submitted to growth assays in leboratory until 8 days after sowing (DAS). In the greenhouse experiment, the seeds were sown in an 8 L pot, which received 4.0 x 108 conidia fo Trichoderma per pot aiming to the soil treatment. In both evaluations were: germination percentage (GP), root length (RL), shoot length (SL), total length (TL), fresh root mass (FRM), fresh shoot mass (FSM), total fresh mass (TFM), dry root mass (DRM), dry shoot mass (DSM), total bioomass (TB), root mass ratio (RMR), shoot mass ratio (SMR) and shoot/root system ratio (S/RS). In the greenhouse experiment, paniculation and grain yield were evaluate at 110 DAS. The treatments with T. harzianum ESALQ 1306 and T. asperellum URM5911 were satisfactory, since they provide a grain yield greater than 2,000 kg ha-1 . In addition, T. harzianum ESALQ 1306 provided the best results for GP, RL, SL, TL, FRM, FSM, TFM, DRM, DSM and TB under greenhouse conditions. The reduced biomass allocation to the root system in seedlings treated with Trichoderma ssp. occurred in the laboratory, being confirmed in a greenhouse assays. In the laboratory experiment the strain T. asperellum URM 5911 was detached from the others and in house of vegetation the strain T. harzianum ESALQ 1306. The use of the strain T. harzianum ESALQ 1306 is recommended for the promotion of wheat growth and yield, as it presented productivity values considered satisfactory.
Keywords: Agentes de Biocontrole; Triticum aestivum; Ácidos húmicos; Biocontrol agents; Triticum aestivum; Humic acid; CIENCIAS AGRARIAS